Manejo de efluentes líquidos mediante gestión ambiental en el camal del distrito El Porvenir - Angulo Zavaleta, Karin Jannet (2011)
The most important sectors in the Province of Trujillo are: "Wholesale and Retail Trade" (49%) and "Industry" (13%). Both concentrate 62% of the total local economic agents. Being, the industry sector one of the most deconcentrated activities, 48% is outside the Trujillo district. The district of El Porvenir, is one of the localities that concentrates the development of activities in the industry and manufacturing sector (presence of tanneries, camales, among others), and the one that contributes the most to the department. Its natural, human and capital resources place it among the most important in the province of Trujillo, as it reflects an "emerging industrial" activity, developed mainly in the central avenues of the district and surrounding areas; the same ones that impact the environment contaminating the air, the soil and the subsoil, and causing the deterioration of the facilities and the sewage system (mainly due to the presence of organic waste) not only of the locality but also of the water treatment infrastructure residuals of the metropolis, which is not prepared for the treatment of this type of waste. The objective of this work is to develop an Environmental Management System for wastewater in the El Porvenir district, based on the ISO 14001 standards and the fundamental principles of the Environmental Management system: application of clean technology and preventive actions before corrective The initial evaluation was carried out between March and November 2010, from which it is concluded that the wastewater from the slaughterhouse exceeds the limits established by current regulations: the BOD5 suspended solids of 8.5 ml / L / h, oils and fats from 100 mg / L; Therefore, proper management of wastewater is necessary. For this, the environmental impacts generated in the municipal camps are determined, the prevention measures of the potentials of impact caused by the waste impacts are identified and the methods of control of the contamination are given